PENGARUH MEDIA SOSIAL INSTAGRAM DAN REPUTASI PERUSAHAAN TERHADAP MINAT BELI KAOS MERK HOUSE OF POLOS DI KOTA TASIKMALAYA - Vina Rahmi Maulida (LP2M Universitas Bina Bangsa, 2022)
This research is motivated by the background that business development from the beginning of the month has increased gradually, until the month of Ramadan and holidays arrives, but after the holidays there is also a gradual decline, this is influenced by various factors, including: People's purchasing power decreased due to the Covid-19 pandemic which affected economic development, Promotion of SME companies to be stagnant because the T-shirt model was a little not up to date, The company's reputation was also disrupted by the covid-19 pandemic, customers/buyers wanted to always be the latest models, while the production of House of Plain T-shirts was a bit monotonous in models and colors. Based on this information, that Instagram can be the most strategic social media to become a marketing medium, Instagram content can be said to be very important because it can influence someone's behavior or interests. This study aims to determine the influence of instagram social media and company reputation partially on the buying interest of consumers of House of Polos T-shirts. This research uses a quantitative approach with a survey method and uses a causal associative method using a quantitative approach. The population studied was 100 respondents. The data collected is in the form of secondary and primary data. Data analysis in this study used Multiple Regression Analysis using SPSS software version 24. Based on the discussion and the results of the study showed that: 1) Instagram social media and company reputation simultaneously have a significant effect on the interest in buying House of Polos Brand T-shirts in Tasikmalaya City. 2) Instagram social media partially has a significant effect on the interest in buying House of Polos Brand T-shirts in Tasikmalaya City. 3) The company's reputation partially has a significant effect on the interest in buying House of Polos Brand T-shirts in Tasikmalaya City